Research trends and content analysis of ocean literacy studies between 2017 and 2021 - Cavas, Bulent; Acık, Sermin; Koc, Simge; Kolac, Mısra (Frontiers in Marine Science, 2023)
Ocean literacy (OL) refers to the ability of citizens to understand and explain the concepts and phenomena related to the oceans, and leads them to positive behavioral change for the protection and sustainability of the oceans. The study presents a bibliometric analysis of ocean literacy-based studies published between 2017 and 2021, in order to provide more meaningful information about (a) the academic journals that mostly publish ocean literacy studies, (b) the content analysis of the articles, (c) country rankings over the years (d) the keywords mostly used and (e) the funding source. The Web of Science (WoS) and Scopus databases were used to find ocean literacy-based articles. Seventy-nine articles from forty ocean literacy academic journals covered by WoS and Scopus were carefully selected using predefined criteria. The results revealed that most of ocean literacy-based articles were published in the Frontiers in Marine Science journal (n=23). The countries that published the most ocean literacy-based articles were UK, Italy, Canada, USA, and Portugal. Most of the studies were supported by governmental budgets (n=44). The most popular concepts in ocean literacy-based studies included "Global OL Perspectives'', "Sustainability", "Citizen Science", "Students' OL Improvement", "Measuring and Evaluating Students and Teachers' OL", "Stakeholders' Effects on OL", "OL Based Books-iBooks-Textbooks" and "Individuals' Affective Domain on OL". By considering the large number of ocean literacy-based articles published in academic journals indexed in WoS and Scopus, this article can contribute significantly to ocean literacy studies and informed and responsible research, as well as to citizen input to policy development on ocean literacy.